KORELASI PERILAKU SPIRITUAL DENGAN TINGKAT KECEMASAN REMAJA DI WILAYAH KERJA PUSKESMAS KASIHAN I BANTUL YOGYAKARTA - Endar Timiyatun; Ardhian Indra Darmawan; Eka Oktavianto; Aris Setyawan (Universitas Respati Yogyakarta, 2021)
Correlation of Spiritual Behavior with the Level of Adolescent’s Anxiety in the Working Area of Primary Health Care Kasihan I Bantul YogyakartaBackground: Anxiety is a psychological response that arises in every individual. Anxious responses that arise in each individual are influenced by internal and external factors of the individual. Psychological response in the form of anxiety is a response that can have an adaptive or maladaptive effect. Coping mechanisms that arise in adolescents are influenced by one of the deep mental values that is spiritual. Objectives: to analyze the relationship between adolescent spiritual behavior with anxiety levels in adolescents. Methods: We have conducted a non-experimental study with a cross-sectional design. This research was conducted in January-Mey 2020. The number of samples in this study were 57 adolescents in Lemahdadi, Bangunjiwo, Kasihan, Bantul. The sampling technique was purposive. The instruments used were the Hamilton Anxiety Rating Scale (HARs) and the Spiritual Intelligence Questionnaire. Kendal tau test was used to analysis test. Results: The majority of adolescent spiritual behavior in the work area of the Kasihan I Health Center are in the good category, namely 49 respondents (86%), the majority of adolescents in the work area of the Kasihan I Health Center do not experience anxiety, which is 51 respondents (89.5%). adolescents who have spiritual behavior in the good category, will tend not to experience anxiety, which is a number of 44 adolescents (77,2%). The better spiritual behavior, the lower the level of anxiety experienced by adolescents (the direction of a negative relationship or inversely related). The p value of the correlation test results using the Chi-Square test of 0.012 (p value <0.05). The correlation coefficient value is -0.456. Conclusion: there is a relationship between adolescent spiritual behavior with anxiety levels experienced by adolescents (p value <0.05).